ANALISIS REALISASI ANGGARAN DAN RENCANA KERJA ANGGARAN SEKOLAH (RKAS) TAHUN ANGGARAN 2016 DAN 2017 PADA SMPIT AL-IZZAH KOTA SERANG - Khristina Sri Prihatin; Nopian Nopian (FKIP, Universitas Banten Jaya, 2020)
This study aimed to determine how the budget realization and work plan for the Al-Izzah Junior High School budget in Serang City for the period 2016 and 2017 and to determine the suitability of the RPP and its realization. In this study, researchers used quantitative research because the data of this study were taken from the plan data and the realization of the school budget in the form of numbers and then examined the correctness. The results of this study found that there were differences between the realization and the budget, such as spending deviations that were not in accordance with school budget allocations and expenditures were not reasonable with predetermined values. It was expected that every activity carried out by school requires an evaluation of the activity program to carry out activities in accordance with what was planned. In preparing the school budget work plan, it was necessary to pay attention to the types, objects and details of expenditure objects that would be needed so that the plan was achieved, and the budget format was required both for reports and realization in accordance with Standard Operating Procedures.